Porous chitosan particles doped by in situ formed silver nanoparticles: Electrorheological response in silicon oil. (8th August 2022) - Kuznetsov, Nikita M.; Kovaleva, Victoria V.; Volkov, Danila A.; Zagoskin, Yuriy D.; Vdovichenko, Artem Yu.; Malakhov, Sergey N.; Bakirov, Artem V.; Yastremsky, Eugeny V.; Kamyshinsky, Roman A.; Stupnikov, Alexei A.; Chvalun, Sergei N.; Grigoriev, Timofei E.
Abstract: Effect of in situ formed silver nanoparticles doping on electrorheological response of highly porous chitosan particles in suspensions of polydimethylsiloxane (silicone oil) is considered. Silver nanoparticles are directly reduced by chitosan from solution. Highly porous chitosan particles with different silver content are fabricated by spraying from solution followed by freeze‐drying. A high and stable electrorheological response of suspensions in wide range of electric field strength is observed at a very low filler content of 1 wt%. The nature of the electrorheological effect is considered from the standpoint of dielectric spectroscopy. The activation energies of polarization processes are determined from the temperature dependences of the dielectric loss modulus. The study shows the opportunity to control the properties of stimuli‐responsive materials by changing the structure and physicochemical properties of the functional filler. This approach opens up new possibilities for creating materials with high performance and predetermined properties.